A New Technique for Investigating Dust Charging in the PMSE Source Region - Mahmoudian, Alireza; Kosch, Michael J.; Vierinen, Juha; Rietveld, Michael T (Geophysical Research Letters, 2020)
This paper was published by AGU. Copyright 2020 American Geophysical Union. A new technique for investigating dust charging in the PMSE (polar mesospheric summer echoes) source region is proposed and discussed in this paper. The first high-frequency (HF) modulation of the PMSE with varying pump power was employed during a recent experimental campaign at EISCAT (European Incoherent Scatter Scientific Association). Two experiment setups including HF pump power stepping as well as quasi-continuous power sweeping were used. The experiment was designed based on a computational model capable of simulation of PMSE evolution during HF pump modulation in order to develop a new approach for studying the dust charging process in the PMSE source region. The charge state of dust particles along with background dusty plasma parameters is estimated using the experimental and computational results. A detailed future experimental design based on background dusty-plasma parameters is proposed.